Three temptations of leaders - Kakabadse, Andrew P.; Kakabadse, Nada K.; Lee-Davies, Linda (Emerald Group Publishing Limited, 2007)
Despite the challenge of precisely defining the nature of temptation, this paper seeks to collect contrasting perspectives of this less attractive side of leadership and sets out to find a cure, or rather prevention, for falling into its grasp.
Keywords: Leadership; Management power